2020
DOI: 10.1101/2020.07.28.226092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct exposure to SARS-CoV-2 and cigarette smoke increases infection severity and alters the stem cell-derived airway repair response

Abstract: SUMMARYMost demographic studies are now associating current smoking status with increased risk of severe COVID-19 and mortality from the disease but there remain many questions about how direct cigarette smoke exposure affects SARS-CoV-2 airway cell infection. We directly exposed mucociliary air-liquid interface (ALI) cultures derived from primary human nonsmoker airway basal stem cells (ABSCs) to short term cigarette smoke and infected them with live SARS-CoV-2. We found an increase in the number of infected … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Thus, the observed synergy can be due to the effects on independent targets. Lastly, we tested berzosertib in a primary human lung tissue culture system consisting of mucociliary air-liquid interface (ALI) cultures derived from primary human tissue (Purkayastha et al, 2020). In this ALI system, as well, berzosertib was effective in inhibiting SARS-CoV-2 (Figures 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the observed synergy can be due to the effects on independent targets. Lastly, we tested berzosertib in a primary human lung tissue culture system consisting of mucociliary air-liquid interface (ALI) cultures derived from primary human tissue (Purkayastha et al, 2020). In this ALI system, as well, berzosertib was effective in inhibiting SARS-CoV-2 (Figures 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Smoking-mediated upregulation of the androgen pathway also leads to an increased SARS-CoV-2 susceptibility [26]. Acute smoke exposure allows for more severe proximal airway epithelial disease from SARS-CoV-2 by reducing the mucosal innate immune response and ABSC proliferation and has implications for disease spread and severity in people exposed to cigarette smoke [27]. The radiological manifestation of COVID-19 is mainly peripheral ground-glass opacity while age, smoking and hypertension were used to predict the severity of COVID-19 disease [28].…”
Section: Resultsmentioning
confidence: 99%
“…44 Purkayastha and colleagues, through modeling the direct effects of cigarette smoke on SARS-CoV-2 infection, showed that acute cigarette smoke exposure increases the number of infected and apoptotic cells, prevents the normal airway basal stem cell repair response, suggesting that smoke increases COVID-19 severity. 46 However, it has been shown that smoking was not associated with increased mortality in COVID-19 pneumonia 47,48 , but cumulative smoking exposure, as measured by pack/years, was associated with a higher risk of hospitalization and mortality from COVID-19 in a dose-dependent manner. 49 In contrast, cigarette smokepretreatment potently abrogates SARS-CoV-2 replication in an vitro model 41 .…”
Section: Discussionmentioning
confidence: 98%